Blacking out - Yvan Lengwiler (University of Basel, Center of Business and Economics (WWZ), 2020)
The partial shutdown of the economy following the outbreak of the COVID-19 pandemic has highlighted the lack of measurements of economic activity that are available with a short lag and at high frequency. The consumption of electricity is a candidate for such a proxy.
Keywords: C50; E01; 330; COVID-19; electricity; seasonal adjustment; weather data